2022
DOI: 10.1039/d1ea00068c
|View full text |Cite
|
Sign up to set email alerts
|

Ice nucleating particles in the Canadian High Arctic during the fall of 2018

Abstract: Ice nucleating particles (INPs) are a small subset of atmospheric particles that can initiate the formation of ice in mixed-phase clouds. Here we report concentrations of INPs during October and...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 79 publications
(230 reference statements)
0
4
0
Order By: Relevance
“…The association between ARs and p‐AARs could be used to understand both how aerosols modify cloud properties and for understanding aerosol wet deposition. BC and DU aerosols are important species when it comes to liquid and mixed‐phase clouds, as BC can act as CCN (Quinn et al., 2011; Zieger et al., 2023) and DU can act as INP (Irish et al., 2019; Kawai et al., 2023; Yun et al., 2022). Therefore, when ARs and p‐AARs are combined, cloud properties could be different compared to AR‐only cases, with impacts on cloud albedo and/or precipitation timing.…”
Section: Potential Applications Of P‐aarsmentioning
confidence: 99%
“…The association between ARs and p‐AARs could be used to understand both how aerosols modify cloud properties and for understanding aerosol wet deposition. BC and DU aerosols are important species when it comes to liquid and mixed‐phase clouds, as BC can act as CCN (Quinn et al., 2011; Zieger et al., 2023) and DU can act as INP (Irish et al., 2019; Kawai et al., 2023; Yun et al., 2022). Therefore, when ARs and p‐AARs are combined, cloud properties could be different compared to AR‐only cases, with impacts on cloud albedo and/or precipitation timing.…”
Section: Potential Applications Of P‐aarsmentioning
confidence: 99%
“…A droplet freezing technique similar to Whale et al (2015) was used to determine the freezing temperature spectrum of aqueous suspensions. We have previously used this technique to study the ice-nucleating properties of inorganic, organic, and environmental INS samples (Irish et al 2019;Worthy et al 2021;Xi et al 2021;Yun et al 2020;Yun et al 2022). Hydrophobic glass slides (Hampton Research HR3-239) were rinsed with ultrapure water, dried with nitrogen gas, and placed on a cold stage (Grant Asymptote EF600 cryocooler).…”
Section: Droplet-freezing Experimentsmentioning
confidence: 99%
“…Recent studies have suggested the importance of Arctic dust as INPs under conditions relevant for the formation of mixed‐phase clouds (Sanchez‐Marroquin et al., 2020; Tobo et al., 2019; Xi et al., 2022; Yun et al., 2022). Tobo et al.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have suggested the importance of Arctic dust as INPs under conditions relevant for the formation of mixed-phase clouds (Sanchez-Marroquin et al, 2020;Tobo et al, 2019;Xi et al, 2022;Yun et al, 2022). Tobo et al (2019) showed that Arctic dust collected from the surface of a glacial outwash plain in the Svalbard Islands has a remarkably high ice nucleating ability, especially at high temperatures (>−20°C), and suggested that this high ice nucleating ability is caused by the presence of certain organic matter contained in the dust.…”
mentioning
confidence: 99%